Public Health Research in Republic of Macedonia as an essential public health function - D. Gudeva Nikovska; F. Tozija; D. GJorgjev (My University, 2009)
Analysis of good governance in public health sector in RM was performed by developing and applying an instrument for evaluation of 10 essential public health functions (EPHF) that are responsibility of health authorities, in order to identify ‘grey zones’ and provide recommendations and directions for improvement. The analysis has been performed using the standardized questionnaire developed by US CDC & PAHO, translated and adapted to be used in Macedonian context. The instrument incorporates 11 EPHF and outlines 49 indicators that are evaluated through answers on questions for measures and submeasures in the defined area. The survey was performed in three stages: translation of the instrument, pre-testing on representative sample of government officials and necessary adaptations made to be used in Macedonian context; interviews with three groups of respondents—central government officials, representatives of government institutions at local level and representatives of NGO and Summary of the results and preparation of final report, including recommendations for remedial activities. Analysis of EPHF#10 Public Health Research shows ‘minimum performance’ by all three groups of respondents. There is partially developed public health research agenda, and key stakeholders are only exceptionally involved in research. There is existing research capacity, but lacking is interdisciplinary approach, regular evaluation of the research priorities, transparency in results dissemination and sharing of results with those concerned with the problem. In the subsequent SWAT analysis, activities for development of institutional capacity for PH research are identified as strength, weakness is in the absence of the agenda for PH research, while threats, or the biggest ‘gray zone’ to be addressed by the health authorities are seen in decision making that is not evidence based.